Diffusion of Technology in the Teaching of Neuroanatomy in Times of Pandemic: A Medical and Academic Perspective on Learning - Brito, Herika Karla Negri; Veiga Silva, Ana Cristina; Lima, Luís Felipe Gonçalves de; Alencar Neto, Joaquim Fechine de; Ferreira Neto, Otávio da Cunha; Lemos, Nilson Batista; Dias, Artêmio José Araruna; Diniz, Andrey Maia Silva; Sanchez, Luana Moury Fernandes; Silva, Melissa Helena Rodrigues; Alves Neto, Luís Bandeira; Lira, Arthur Oliveira; et al. (Frontiers in Surgery, 2022)
The Covid-19 pandemic has caused major changes in many sectors of society worldwide. The issue of medical education stands out since it had to adapt to the rules of social isolation, ensuing discussions about the computerization of teaching methodology, particularly in neuroanatomy. In particular, the latter showed greater adaptability to new technologies and highly promising learning results. During this review, we aim to evaluate the current state of neuroanatomy teaching and evaluate the possibilities of incorporating technology into teaching-learning of human anatomy in a post-pandemic world.